Temporomandibular disorders in a young adolescent brazilian population: Epidemiologic characterization and associated factors - Franco-Micheloni, Ana Lucia [UNESP]; Fernandes, Giovana [UNESP]; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Camparis, Cinara Maria [UNESP] (MRE Press, 2015)
Aims: To carry out an epidemiologic characterization of the most common subtypes of temporomandibular disorders (TMD) and to identify associated factors in a Brazilian sample of young adolescents. Methods: From a population of public schoolchildren (12 to 14 years of age), 3,117 students were randomly invited to participate in this study. TMD was assessed according to the Research Diagnostic Criteria for TMD (RDC/TMD) Axis I, in addition to some questions of the Axis II history questionnaire. The associated factors, ie, difficulty with concentration/attention, anger, sadness, anxiety, headache complaints, oral parafunctions, diurnal jaw clenching, tooth grinding at night, and parents not living together, were assessed based on the responses of the adolescents and their parents to structured questions. For the statistical analyses, descriptive statistics, chi-square tests, odds ratio, and logistic regression models were used, adopting a 95% confidence interval and 5% level of significance. Results: The sample consisted of 1,307 individuals (response rate of 41.9%), 56.8% (n = 742) girls. Overall, 397 (30.4%) adolescents presented with TMD, of whom 330 (25.2%) had painful TMD diagnoses. The majority of these had painful TMD of muscular origin (13.1%) and comprised chronic cases (14.9%). Girls presented higher frequencies of TMD overall, painful TMD, painful combined TMD, and chronic painful TMD diagnoses The final multivariate logistic regression model revealed that headache complaints (odds ratio 2.87; confidence intervals 2.21-3.72), oral parafunctions (2.08; 1.26-3.44), tooth grinding at night (2.05; 1.56-2.70), diurnal jaw clenching (1.96; 1.50-2.55), and parents not living together (1.38; 1.07-1.80) were the factors significantly associated with a TMD (overall) diagnosis. Conclusion: About 25% of the adolescents evaluated presented painful TMD, and the majority of these comprised muscular and chronic cases. Some factors, such as reports of headache complaints, oral parafunctions, tooth grinding at night, and parents not living together, were associated with this condition among young Brazilian adolescents. Special attention should be given to these factors among adolescents with TMD.
Keywords: Adolescents; Epidemiology; Prevalence; Temporomandibular joint disorders